Comparison of peak vertical force and vertical impulse in the inside and outside hind limbs in horses circling on a soft surface, at trot and canter - Crevier-Denoix, N.; Munoz-Nates, F.; Camus, M.; Ravary-Plumioen, B.; Denoix, J. M.; Pourcelot, P.; Chateau, H. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
In horses, lameness is often more pronounced on a circle, compared to straight line (Ross and Dyson, 2011). At trot, some lameness conditions worsen when the affected limb is on the inside of the circle while others worsen when the affected limb is on the outside. In addition to asymmetrical loading of the anatomical structures (e.g. loading of the medial structures increased on the outside limb), an increased overall loading of the outside limb has been demonstrated in the forelimb. In horses circling at trot, Chateau et al. (2013) using a dynamometric horseshoe, demonstrated that the peak vertical force during stance is significantly larger on the outside forelimb. However to date, no kinetic data is available in the hind limb.